Factors Influencing Undergraduates’ Engagement and Satisfaction with Online Teaching in Chengdu, China - Li, Luo (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The research aimed to examine the factors influencing undergraduates' engagement and satisfaction with online teaching in Chengdu, China. The conceptual framework proposed the relationships among Teachers' self-efficacy, Teachers' technical readiness, Teachers' empathy, Teachers' responsiveness, Students' sensory requirements, Students' engagement and Students' satisfaction. Research design, data and methodology: The researcher used multistage sampling techniques to select the sample. A questionnaire survey was conducted among 500 undergraduates from Xihua University in Chengdu, China. Cronbach's Alpha was used to assess the reliability, while skewness and kurtosis tests evaluated data normality. Confirmatory Factor Analysis (CFA) was performed to ensure the model’s validity and, and Structural Equation Modeling (SEM) was used to assess model fit and test hypotheses. Results: The results explicated that teachers' self-efficacy and teachers' technical readiness have significant influence on students' engagement. Teachers' self-efficacy, teachers' technical readiness, teachers' responsiveness, teachers' empathy, students' sensory requirements and students' engagement have significant influence on students' satisfaction. Conclusions: Eight hypotheses were proven to fulfil the research objectives. Universities are suggested to continuously enhance teachers' self-efficacy and online teaching techniques, while also prioritizing students' reactions and emotional well-being. Additionally, fostering students' engagement in online teaching can effectively improve students' satisfaction with online teaching, ultimately leading to better learning outcomes.